NATO Burden Sharing Research along Three Paradigms. Issue 5 (4th July 2022) - Bogers, Marion; Beeres, Robert; Bollen, Myriame
ABSTRACT: This paper provides both a quantitative and a qualitative review and interpretation of 153 journal papers on NATO burden sharing behaviour published over the period 1966–2020. Based on our findings, we distinguish three paradigms, reflecting the main questions and views within their particular realm of burden sharing research. Subsequently, these three paradigms study (1) the distribution of defence burdens amongst NATO member states; (2) the determinants of NATO burden sharing behaviour; and (3) how contributions to the public good of individual member states merge to determine the overall level of the good available for consumption. For each paradigm, a qualitative insight in evolving bodies of literature is offered. As it turns out, most burden sharing studies are limited to one paradigm and its ensuing main question. Future research may benefit from cross-fertilization across paradigms, longitudinal approaches and a widening of empirical foci to encompass novel threats.